Embryo transfer impact: a comprehensive national cohort analysis comparing maternal and neonatal outcomes across varied embryo stages in fresh and frozen transfers - Chang, Chih-Ting; Weng, Shih-Feng; Chuang, Hui-Yu; Hsu, I-Le; Hsu, Chia-Yi; Tsai, Eing-Mei (Frontiers in Endocrinology, 2024)
study included 51,762 eligible female participants who underwent ART and embryo transfer. Pregnancy outcomes, maternal complications, and singleton neonatal outcomes were evaluated using the National Health Insurance Database from January 1st, 2013, to December 31st, 2018. Cases were categorized into groups based on whether they underwent fresh or frozen embryo transfers, with further subdivision into cleavage stage and blastocyst stage transfers. Exposure variables encompassed clinical pregnancy rate, live birth rate, OHSS, pregnancy-induced hypertension, gestational diabetes mellitus (DM), placenta previa, placental abruption, preterm premature rupture of membranes (PPROM), gestational age, newborn body weight, and route of delivery.Frozen blastocyst transfers showed higher rates of clinical pregnancy (CPR) and live births (LBR) compared to fresh blastocyst transfers. Conversely, frozen cleavage stage transfers demonstrated lower rates of clinical pregnancy and live birth compared to fresh cleavage stage transfers. Frozen embryo transfers were associated with reduced risks of OHSS but were linked to a higher risk of pregnancy-induced hypertension compared to fresh embryo transfers. Additionally, frozen embryo transfers were associated with a higher incidence of large for gestational age infants and a lower incidence of small for gestational age infants.The freeze-all strategy may not be suitable for universal application. When embryos can develop to the blastocyst stage, FET is a favorable choice, but embryos can only develop to the cleavage stage, fresh embryo transfer becomes a more reasonable option.